Analisis Pola Persebaran dan Jangkauan Pelayanan Fasilitas Kesehatan terhadap Permukiman dengan Sistem Informasi Geografis (SIG) di Kabupaten Boyolali Tahun 2025 - Lutfi Ardiansyah; M. Iqbal Taufiqurrahman Sunariya; Choirul Amin; Basyar Ihsan Arijuddin (Mataram University, 2026)
Health services are an important factor for a region because good health services indicate a better quality of life for the community. The coverage and availability of health services are also important factors in supporting optimal health facilities. However, the distribution and service coverage of health facilities are still uneven, resulting in several areas being inadequately served, especially in peripheral and highland areas. This study uses a Geographic Information System (GIS) approach to analyze the distribution patterns and service coverage of health facilities in Boyolali Regency in 2025. The methods used in this study include buffer analysis and Average Nearest Neighbor (ANN) analysis. ANN analysis was used to identify distribution patterns, while buffer analysis was used to measure the service coverage of health facilities in residential areas. The data used were obtained from the locations of health facilities in Boyolali Regency, including hospitals, community health centers, and clinics. The results showed that the distribution pattern of health facilities in Boyolali Regency in 2025 tended to be concentrated in the central area of the regency, especially in Boyolali, Teras, and Mojosongo Districts, which have better accessibility and higher population density. The results of the Average Nearest Neighbor analysis showed that the distribution pattern of health facilities was clustered and statistically significant, with a ratio value of 0.620092, a z-score of -6.541112, and a p-value of 0.000000. The results of the service coverage analysis using a 3000-meter buffer radius showed that there were still areas that had not been optimally covered by health facilities, especially in peripheral and highland districts. These conditions were influenced by topography, accessibility, road networks, and population concentration. Overall, this study indicates that there are inequalities in the distribution and service coverage of health facilities in Boyolali Regency in 2025. Therefore, it is necessary to improve the equitable distribution of health facilities and accessibility through road infrastructure development to support transportation in peripheral and highland areas that are still inadequately served so that health services can operate optimally.